Three classifications on branching processes and their behavior for finding the solution of nonlinear integral equations - Vajargah, Behrouz Fathi; Moradi, Mojtaba (Mathematical Modelling and Analysis, 2010)
In this paper, we consider the Monte Carlo method for finding the solution of nonlinear integral equations at a fixed point xo‐ In this method, simulated Galton‐Watson branching process is employed for solving the proposed integral equation. The main goal of this paper is to compare the behavior of three classifications of branching process based on the mean progeny, i.e. the subcritical, critical and supercritical process. First published online: 09 Jun 2011